Interactions between D-ala-met-enkephalin, A10 dopaminergic neurones, and spontaneous behaviour in the rat. - Kelley, A; Stinus, L; Iversen, S (1980)
We have investigated the interaction between opioid peptides and dopaminergic A10 (DA-A10) neurones in the ventral tegmental area (VTA). The behavioural consequences of VTA infusion of d-Ala-Met-enkephalinamide (DALA) were analyzed. DALA elicited a dose-dependent increase in locomotor activity measured in photocell cages and the circular corridor. Observations in the open field and in a hole box revealed that DALA-induced behavioural stimulation was characterized by enhancement of locomotion, rearing, and number of hole visits, while grooming time and duration of hole visits were decreased. DALA-induced stimulation was reserved by naloxone, and was completely blocked by 6-OHDA destruction of DA-A10 terminals. d-Amphetamine-induced behavioural activation was potentiated by simultaneous VTA infusion of DALA which indicates that the behavioural response to DALA is dependent on DA-A10 neuronal activity. It is postulated that stimulation of opiate receptors exerts a presynaptic inhibition of an inhibitory input to DA-A10 neurones (eg. GABA or dendritic DA), thus releasing dopaminergic activity. In contrast to the acute effect, the d-amphetamine response was strongly attenuated 4 h, 1 and 6 days after VTA infusion of DALA, and returned to normal only at 14 days. This long-lasting modification may reflect decreased activity of opioid neurones, releasing the inhibition of DA-A10 neurones. Our findings suggest that endogenous opioid peptides may exert a modulatory influence on the dopaminergic mesocorticolimbic system.